2016
DOI: 10.3390/ijerph13050495
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Prenatal Exposures to Environmental Chemicals on Birth Weight

Abstract: Prenatal chemical exposure has been frequently associated with reduced fetal growth by single pollutant regression models although inconsistent results have been obtained. Our study estimated the effects of exposure to single pollutants and mixtures on birth weight in 248 mother-child pairs. Arsenic, copper, lead, manganese and thallium were measured in cord blood, cadmium in maternal blood, methylmercury in maternal hair, and five organochlorines, two perfluorinated compounds and diethylhexyl phthalate metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 63 publications
(67 reference statements)
4
55
1
1
Order By: Relevance
“…Larger studies with improved precision and accounting for multiple pollutants are needed to confirm this possibility and whether PFAS associations with birth outcomes indeed differ according to sex. In regard to mercury, findings from this and recent birth cohort studies, with reported lower mercury exposure levels compared to older birth cohorts, do not clearly support associations with birth size measures (Govarts et al 2016; Murcia et al 2016; Vrijheid et al 2016); however, associations of maternal low-level mercury exposure with adverse neurodevelopmental outcomes in the offspring in recent birth cohorts are well documented (Vrijheid et al 2016), adding to mounting evidence of mercury toxicity.…”
Section: Discussioncontrasting
confidence: 78%
“…Larger studies with improved precision and accounting for multiple pollutants are needed to confirm this possibility and whether PFAS associations with birth outcomes indeed differ according to sex. In regard to mercury, findings from this and recent birth cohort studies, with reported lower mercury exposure levels compared to older birth cohorts, do not clearly support associations with birth size measures (Govarts et al 2016; Murcia et al 2016; Vrijheid et al 2016); however, associations of maternal low-level mercury exposure with adverse neurodevelopmental outcomes in the offspring in recent birth cohorts are well documented (Vrijheid et al 2016), adding to mounting evidence of mercury toxicity.…”
Section: Discussioncontrasting
confidence: 78%
“…With the more direct exposure measures and combinations of stressors and confounding factors that are examined in epidemiological studies, it is more important for statistical modeling challenges to be considered (e.g., type II errors from insufficient statistical power to detect associations or statistical interactions, multicollinearity amongst mixtures) . Principal components regression and meta‐regression analyses may offer solutions to some of these challenges . As with risk characterization of chemical mixtures, another helpful strategy is to use information on individual stressors and pairwise interactions to quantify risk estimates for the different stressor combinations.…”
Section: Example Risk Characterization Approaches For Crasmentioning
confidence: 99%
“…In addition, people who live near these contaminated sites are generally low-income families with a higher level of vulnerability to the toxic effects of pollutants. Some evidence from geo-statistical studies reflect that the distribution of learning disorders and other health outcomes, coincides with the historical presence of significant sources of heavy metals and contextual factors such as low quality of housing, poverty, low educational attainment of the parents and other factors associated with the neighborhood (Govarts et al 2016, Margai and Henry 2003, Olivas-Calderon et al 2015, Rauh et al 2008, Tsuji et al 2015, Zeng et al 2016). This issue of environmental injustice has been documented throughout the world in many different countries (Claudio 2007, Cutter 2006).…”
Section: Introductionmentioning
confidence: 99%